Case studies in environmentally responsible design - American Institute of Architects (New York : American Institute of Architect, 1994)
Using a series of case studies, originally aired as video-conferences during 1993, this video examines the principles of environmentally responsible design. Highlighted are the Audubon Society Headquarters in New York, N.Y.; the Way Station in Frederick, MD.; the Rocky Mountain Institute in Snowmass, CO; the NMB Bank in the Netherlands; the Westbend Mutual Insurance headquarters in West Bend, Wisc.; and the Greening of Harlem, New York, N.Y
Title from title screen
DVD format
Keywords: Sustainable architecture -- Case studies; Architecture and energy conservation; Land use -- Environmental aspects -- United States